Identity and uncertainty: art-mediated medical student reflections in a time of transition. Issue 1 (31st December 2022) - Robledo-Gil, Talia; Ryznar, Elizabeth; Chisolm, Margaret S.; Balhara, Kamna S.
ABSTRACT: Medical education comprises intense periods of transition, which can significantly impact student well-being, as well as personal and professional development. In 2020, medical students navigating transitions from pre-clinical to clinical roles were also experiencing the historic forces of the COVID-19 pandemic and ongoing societal reckoning with systemic injustice and racism, likely heightening the usual challenges associated with these transitions. Reflection has been suggested as a tool for facilitating such transitions, and arts-mediated approaches hold promise in inspiring authentic reflection, yet they are rarely used to prompt medical student reflection. This article describes common themes in medical students' reflections on a specific period of transition during a unique moment in history, via qualitative analysis of their narrative responses to visual arts-mediated reflective prompts. The authors used a visual arts-based activity to explore medical students' hopes and concerns as they transitioned to clinical clerkships between the 2019–2020 and 2020–2021 academic years at one academic institution. Qualitative analysis using an exploratory constructivist approach revealed that students' reflections often focused on identity within three main themes: the personal self, the professional self, and the social self. Within these categories, subthemes included uncertainty and concerns focusing on medical training and knowledge, the sense of hope and value inherent to their social connections, critiques of the culture of medical education, and reflections on complicity and responsibility in racial injustice. This article not only provides a cross-sectional snapshot of the experiences of medical students during a historic moment, but also provides themes to guide discussions on training transitions and describes a low-cost, adaptable approach to facilitating deep exploration and reflection on tumultuous moments in training.